The role of N-acetylcysteine in osteogenic microenvironment for bone tissue engineering - Zheng, Haowen; Liu, Jiacheng; Sun, Lanxin; Meng, Zhaosong (Frontiers in Cell and Developmental Biology, 2024)
Bone defect is a common clinical symptom which can arise from various causes. Currently, bone tissue engineering has demonstrated positive therapeutic effects for bone defect repair by using seeding cells such as mesenchymal stem cells and precursor cells. N-acetylcysteine (NAC) is a stable, safe and highly bioavailable antioxidant that shows promising prospects in bone tissue engineering due to the ability to attenuate oxidative stress and enhance the osteogenic potential and immune regulatory function of cells. This review systematically introduces the antioxidant mechanism of NAC, analyzes the advancements in NAC-related research involving mesenchymal stem cells, precursor cells, innate immune cells and animal models, discusses its function using the classic oral microenvironment as an example, and places particular emphasis on the innovative applications of NAC-modified tissue engineering biomaterials. Finally, current limitations and future prospects are proposed, with the aim of providing inspiration for targeted readers in the field.